2020
DOI: 10.1038/s41523-020-00175-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrating single-cell RNA-sequencing and functional assays to decipher mammary cell states and lineage hierarchies

Abstract: The identification and molecular characterization of cellular hierarchies in complex tissues is key to understanding both normal cellular homeostasis and tumorigenesis. The mammary epithelium is a heterogeneous tissue consisting of two main cellular compartments, an outer basal layer containing myoepithelial cells and an inner luminal layer consisting of estrogen receptor-negative (ER − ) ductal cells and secretory alveolar cells (in the fully functional differentiated tissue) and hormon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…In particular, our observations agree with previous ndings that luminal-like cells acquire basal-like features following oncogenic or homeostatic disruption (Hein et al, 2016;Lim et al, 2009;Meyer et al, 2011;Molyneux et al, 2010;Van Keymeulen et al, 2015;Wahl and Spike, 2017;Wuidart et al, 2018). Conversely, we cannot rule out the possibility that the LB population arises from basal-like cells, consistent with basalcompartment cells giving rise to luminal cells in proposed hierarches of normal mammary gland development (Fu et al, 2020;Regan and Smalley, 2020), and with studies showing that adult committed basal cells can be reprogrammed to acquire more luminal-like states (Koren et al, 2015;Lilja et al, 2018;Van Keymeulen et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…In particular, our observations agree with previous ndings that luminal-like cells acquire basal-like features following oncogenic or homeostatic disruption (Hein et al, 2016;Lim et al, 2009;Meyer et al, 2011;Molyneux et al, 2010;Van Keymeulen et al, 2015;Wahl and Spike, 2017;Wuidart et al, 2018). Conversely, we cannot rule out the possibility that the LB population arises from basal-like cells, consistent with basalcompartment cells giving rise to luminal cells in proposed hierarches of normal mammary gland development (Fu et al, 2020;Regan and Smalley, 2020), and with studies showing that adult committed basal cells can be reprogrammed to acquire more luminal-like states (Koren et al, 2015;Lilja et al, 2018;Van Keymeulen et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…S1B). Further gene expression analysis identified a series of genes, previously described to define specific lineage states of mammary epithelial populations, to be also expressed by cells from non-epithelial clusters [18,21,33,34] (Supplementary Fig. S1C).…”
Section: Defining Mammary Epithelial and Non-epithelial Cell Populationsmentioning
confidence: 99%
“…The arrows serve to suggest that cells tending toward a bipotential progenitor fate (mEC9) give rise to myoepithelial progenitors (mEC1) and predicted luminal common progenitors (mEC7). (D) Feature UMAP plots showing expression levels of specific genes in mEC clusters ◂ previously proposed to define a progenitor-like state, such as E74 Like ETS Transcription Factor 5 (Elf5), Monocyte differentiation antigen 14 (Cd14), KIT Proto-Oncogene, Receptor Tyrosine Kinase (Kit) and Enhancer Of Zeste 2 Polycomb Repressive Complex 2 Subunit (Ezh2), [8,18,21,49,50]. These results suggest an accumulation of partially differentiated luminal secretory cells in mammary tissue from a never pregnant, post-pubescent female mouse.…”
Section: Improving the Classification Of Mammary Epithelial Cell Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study suggested that the expression of miRNAs could be specific to different cells [ 181 ]. The access to single cell RNA-seq, already used in breast cancer studies [ 182 , 183 ], will provide a deeper understanding of fine regulatory mechanisms of milk synthesis.…”
Section: Discussionmentioning
confidence: 99%